A nontoxic fungal natural product modulates fin regeneration in zebrafish larvae upstream of FGF‐WNT developmental signaling. Issue 2 (21st September 2020) - Cavanah, Paul; Itou, Junji; Rusman, Yudi; Tahara, Naoyuki; Williams, Jessica M.; Salomon, Christine E.; Kawakami, Yasuhiko
Abstract: Background: The regeneration of larvae zebrafish fin emerged as a new model of regeneration in the last decade. In contrast to genetic tools to study fin regeneration, chemical probes to modulate and interrogate regeneration processes are not well developed. Results: We set up a zebrafish larvae fin regeneration assay system and tested activities of natural product compounds and extracts, prepared from various microbes. Colomitide C, a recently isolated product from a fungus obtained from Antarctica, inhibited larvae fin regeneration. Using fluorescent reporter transgenic lines, we show that colomitide C inhibited fibroblast growth factor (FGF) signaling and WNT/β‐catenin signaling, which were activated after larvae fin amputation. By using the endothelial cell reporter line and immunofluorescence, we showed that colomitide C did not affect migration of the blood vessel and nerve into the injured larvae fin. Colomitide C did not show any cytotoxic activities when tested against FGF receptor‐amplified human cancer cell lines. Conclusion: Colomitide C, a natural product, modulated larvae fin regeneration likely acting upstream of FGF and WNT signaling. Colomitide C may serve as a template for developing new chemical probes to study regeneration and other biological processes. Key Findings: We performed screening of natural products on zebra fish larvae fin regeneration. Colomitide C inhibited larvae fin regeneration. Colomitide C downregulated FGF and WNT signaling, but did not affect endothelial cells and the nerve. In vitro assays demonstrate that colomitide C has low or no cytotoxicity.